Identify Policies and Future Agenda for Inclusive Education in Indonesia - Bahri, Efri Syamsul; Buwis (Journal of Psychology and Sustainable Education, 2025)
This research aims to identify the meaning, policies and future agenda of inclusive education in Indonesia. This research uses qualitative methods with a descriptive approach and a literature study. Data was obtained randomly from reference literature on the Google Scholar platform. The results of this research show that the implementation of inclusive education in Indonesia refers to the Constitution of 1945 Article 28H paragraph (2), which states that everyone has the right to receive facilities and special treatment to obtain the same opportunities and benefits to achieve equality and justice. The Government and Regional Governments must support the successful implementation of inclusive education, contributing to equal opportunities and benefits to achieve equality and justice. Teachers in inclusive schools also need support to obtain education at a higher level and improve the quality of inclusive education in Indonesia.